2014
DOI: 10.1016/j.tranon.2014.04.001
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Analysis of CXCL12 Isoforms in Breast Cancer1,2

Abstract: CXCL12-CXCR4-CXCR7 signaling promotes tumor growth and metastasis in breast cancer. Alternative splicing of CXCL12 produces isoforms with distinct structural and biochemical properties, but little is known about isoform-specific differences in breast cancer subtypes and patient outcomes. We investigated global expression profiles of the six CXCL12 isoforms, CXCR4, and CXCR7 in The Cancer Genome Atlas breast cancer cohort using next-generation RNA sequencing in 948 breast cancer and benign samples and seven bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 60 publications
0
43
0
Order By: Relevance
“…MELK gene expression was correlated to every sequenced gene in the TCGA breast dataset and genes that were significantly positively or negatively correlated with MELK expression were retained within the gene set. These gene lists were then input into GSEA as described previously (32). GSEA identified that of the top 10 nominated positively associated concepts, three were DNA damage-related, and four were cell-cycle regulation-related (Supplementary Fig.…”
Section: Gsea Analysis Identifies Dna Damage Repair Strongly As Beingmentioning
confidence: 99%
“…MELK gene expression was correlated to every sequenced gene in the TCGA breast dataset and genes that were significantly positively or negatively correlated with MELK expression were retained within the gene set. These gene lists were then input into GSEA as described previously (32). GSEA identified that of the top 10 nominated positively associated concepts, three were DNA damage-related, and four were cell-cycle regulation-related (Supplementary Fig.…”
Section: Gsea Analysis Identifies Dna Damage Repair Strongly As Beingmentioning
confidence: 99%
“…ACKR3 is overexpressed in >30% of all breast cancers (including in situ and invasive ductal and lobular carcinomas), with 97% of studied specimens (106 of 109) exhibiting robust vascular ACKR3 staining with undetectable expression in normal breast tissues (10,15). This overexpression is correlated with poor overall survival and lung metastasis-free survival in patients with invasive ductal carcinomas as well as reduced relapse-free survival in patients with ER+ breast cancer (14,16).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, the expression profiles of the six CXCL12 isoforms and both receptors have been investigated in a large clinical cohort and common breast cancer cell lines. As result, isoform-specific differences in expression and breast cancer outcomes have been established, while CXCR4 and CXCR7 showed an opposite pattern in cancer as compared with normal and further differences between hormone receptor status and molecular subtypes (Zhao et al, 2014).…”
Section: Breast Cancermentioning
confidence: 99%